Hubungan Perilaku Cuci Tangan Perawat Terhadap Pencegahan Infeksi Nosokomial - Romauli Batubara, Anita; Parmin, Selamat; Wulan Safitri , Serli (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
In Indonesia, nosocomial infections reach 15.74%, far above developed countries which range from 4.8 - 15.5%. Hand hygiene is one of the applications of nurses in preventing nosocomial infections. The purpose of the study was to determine the relationship between nurses’ handwashing behavior and the prevention of nosocomial infections in hospitals in Bukit Asam Medika in 2024. The type of research is descriptive analytical with a cross-sectional approach. The study was conducted from April to July 2024. The population in the study were all nurses working at Bukit Asam Medika Hospital in 2024, with a population of 147 nurses. Simple Random Sampling, namely each member or unit of the population has an equal opportunity to be selected as a sample of 60 people. Data were collected using a questionnaire, the data was processed computerized with the Chi-square test. Based on the results of the study showed (66.7%) respondents with good therapeutic communication, (53.3%) respondents with high knowledge, (63.3%) respondents with positive attitudes and (60%) respondents with low emotions. The results of the analysis showed a relationship between knowledge (p value = 0.007), attitude (p value = 0.015) and